2016
DOI: 10.1002/adma.201601391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Conjugated Polymers for Solar Cells: An Updated Report

Abstract: The device efficiency of polymer:fullerene bulk heterojunction solar cells has recently surpassed 11%, as a result of synergistic efforts among chemists, physicists, and engineers. Since polymers are unequivocally the "heart" of this emerging technology, their design and synthesis have consistently played the key role in the device efficiency enhancement. In this article, the first focus is a discussion on molecular engineering (e.g., backbone, side chains, and substituents), then the discussion moves on to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
115
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(116 citation statements)
references
References 67 publications
1
115
0
Order By: Relevance
“…Stabilization of both the highestoccupied molecular orbital and the lowestunoccupied molecular orbital through the addition of electron withdrawing fluorine atoms is a common approach to increase the V oc . [28][29][30] Reductions in recombination (and the subsequent increase in J sc ) upon fluorination have also been widely reported, these, however, are often explained by more favorable microstructure and domain compositions of the active layers, or increased polarization of the exciton, which reduces bimolecular and geminate recombination respectively. [28,[31][32][33] With the high level of interest in backbone fluorination for organic semiconductors and conjugated polymers, we decided to explore the effects of such fluorination on the dielectric constant of the benchmark materials that are poly(3alkylth iophenes) (P3AT).…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization of both the highestoccupied molecular orbital and the lowestunoccupied molecular orbital through the addition of electron withdrawing fluorine atoms is a common approach to increase the V oc . [28][29][30] Reductions in recombination (and the subsequent increase in J sc ) upon fluorination have also been widely reported, these, however, are often explained by more favorable microstructure and domain compositions of the active layers, or increased polarization of the exciton, which reduces bimolecular and geminate recombination respectively. [28,[31][32][33] With the high level of interest in backbone fluorination for organic semiconductors and conjugated polymers, we decided to explore the effects of such fluorination on the dielectric constant of the benchmark materials that are poly(3alkylth iophenes) (P3AT).…”
Section: Introductionmentioning
confidence: 99%
“…Polymers possess light weight, high specific strength and modulus, excellent electrical insulating properties, good processability, excellent chemical stability, and low cost [1][2][3][4][5][6] and have been widely applied in the fields of electronics [7], biology [8], medicine [9], energy [10], and manufacturing industry [11], etc. Unfortunately, the intrinsic low thermally conductive coefficient (λ) and insufficient thermal stability of polymeric matrix have restricted its broader application in the areas which require good heat dissipation and low thermal expansion [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, BHJ OSCs have achieved laboratory efficiencies of around 10% in the conversion of solar to electrical energy, below that reached by inorganic solar cells (some around 40%). To improve the efficiency of BHJ OSCs, one of the options is to study/produce new organic materials for application in the active layer that have better intrinsic properties than those that are already used , . Current works have focused on the search for new electron donor polymers,, since the derivatives of fullerenes used as electron acceptors are already well established in this area …”
Section: Introductionmentioning
confidence: 99%
“…The use of chemical substitutions in existing organic materials has been a very useful tool when it is desired to modify electronic properties , . In previous works we have shown that chemical substitutions carried out in the monomeric units of polymers already employed in OSCs, such as poly(3‐hexylthiophene) (P3HT) and polythieno[3,4‐ b ]thiophene‐ co ‐benzodithiophene (PTB7), resulted in new electron donor materials that presented better bandgaps, solubility and/or ionization potential , .…”
Section: Introductionmentioning
confidence: 99%